Variations in the Prevalence of Female Genital Mutilation Among Reproductive-aged Women in Nigeria Across Three Generations - Chidimma Ezenwa Anyanwu; Kwasi Torpey; Olaiya Paul Abiodun; Olaniyi Felix Sanni; Ifeanyi Donald Anyanwu (Global Health and Education Projects, Inc., 2022)
Background and Objective: Female genital mutilation (FGM) is widespread mainly in low and middle-income countries. Nigeria is one of the countries with the highest prevalence of FGM, accounting for about one of every four cases globally. The purpose of this study was to determine the prevalence of FGM amongthree generations in Abuja, the federal capital city of Nigeria. Methods: This is a cross-sectional study among women of reproductive age (15-49 years) within two area councils of Abuja (Bwari and Abuja Municipal) and Nyanya suburban district adjoining the federal capital territory in Nigeria. The respondents are pregnant women attending antenatal care at four selected health facilities. Data were collected using Google Forms and were analyzed with SPSS for Windows version 25. Results: This study comprised data from 634 females (who had an average age of 33±6.0 years) from four major healthcare facilities in Abuja. The most common age group was 30 - 34 years (29.2%). The prevalence of FGM in the first generation (37.7%) was significantly higher than in the second (28.5%) and the third generations (8.7%) (p<0.01). The prevalence of FGM in the second generation was also significantly higher than in the third (p<0.01). The predictors of women circumcising their daughters include primary/no-education AOR 1.48 (95% CI: 0.41-5.31; p<0.05), being a traditionalist 4.94 (95% CI: 0.29-84.56; p<0.05), or Muslim 2.27 (95% CI: 0.94-5.49; p<0.05), respondent's mother being circumcised 1.69 (95% CI: 0.26-10.85, p<0.05) or mother's circumcision unknown 5.41 (95% CI: 0.78-37.34; p<0.05), respondents being circumcised 54.71 (95% CI: 0.78-37.34; p<0.001), culture 2.48 (95% CI: 1.00-6.19; p<0.05), and ignorance of adverse psycho-social/emotional effects of FGM 4.39 (95% CI: 1.46-13.17; p<0.05). Conclusion and Global Health Implications: Although there is a decline in FGM prevalence from the first generation to the third generation in Nigeria, the current prevalence of 8.7% remains a public health concern. Nigerian women's ongoing experience of FGM requires both individual and stakeholders' involvement to eradicate health-related problems such as tissue damage, infection, scarring, infertility, and pains during sexual intercourse, urination, and menstruation.   Copyright © 2022 Anyanwu et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.